2003
DOI: 10.1046/j.1365-2648.2003.02645.x
|View full text |Cite
|
Sign up to set email alerts
|

Tiredness and fatigue in the postnatal period

Abstract: On the basis of this analysis, it is suggested that childbirth education could be extended to foster more realistic expectations and more effective coping skills to facilitate women's adjustment to motherhood. The possibility of midwives educating mothers about the need to access, recruit and delegate some household activities to willing helpers is addressed. We propose that midwives can help women to have more realistic expectations about life after the birth, by providing advice and legitimizing the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 29 publications
1
65
0
2
Order By: Relevance
“…Most of the predictors found in the present study were also reported to be related to PP fatigue in other studies [7][8][9][11][12][13][14]. A higher maternal age and higher level of state anxiety, an aspect of mental health, have previously been found to be related to PP fatigue [33].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Most of the predictors found in the present study were also reported to be related to PP fatigue in other studies [7][8][9][11][12][13][14]. A higher maternal age and higher level of state anxiety, an aspect of mental health, have previously been found to be related to PP fatigue [33].…”
Section: Discussionsupporting
confidence: 84%
“…In the literature, a plea has been made already a long time ago to prepare women during the antenatal period in order to reduce the likelihood of PP fatigue [9,38]. It has been argued that reducing unrealistically high expectations, and teaching skills for enlisting help from family and social network might be important to prevent severe fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…For 81 mothers attending a private mothercraft unit for infant sleep and crying issues, clinically significant exhaustion was associated with impaired daytime functional efficiency and clarity of thinking (Fisher, Feekery, & Rowe, 2004). It has also been argued that fatigue may impact upon parents' ability to adequately care for and interact with their children (Bayer et al, 2007;McQueen & Mander, 2003). In two qualitative studies, parents of newborns reported that tiredness significantly affects performance in everyday life (Nyberg & Sternhufvud, 2000), and is associated with irritability, limited patience, and decreased ability to cope with infant crying (Nash, Morris, & Goodman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A further reason to support extended postpartum care is that new mothers will get a chance to get enough rest. McQueen and Mander (2003) describe tiredness and fatigue as one of the major problems of new mothers, but they have no clear recommendation to alleviate this. One of their suggestions is more professional support at home, for instance by increasing the number of 'routine' visits of the midwife (thereby increasing the costs) and another is to adopt the Chinese model of informal intensive family support, but neither are regarded as very realistic.…”
Section: The Merits Of Postpartum Care Dutch Stylementioning
confidence: 99%
“…The postpartum period is often, for first-time parents as well as for parents with older children, a time of many questions and insecurities (Fredriksson et al, 2003). Many new parents experience feelings of tiredness and difficulty in sleeping (McQueen and Mander, 2003). At the same time they are expected to be happy and content and to adjust without much difficulty.…”
Section: Introductionmentioning
confidence: 99%